A Novel Optimized Gauss Integral for Transmission Line Voltage Measurement - Zhang, Jiaming; Tan, Zejie; Xu, Zhenheng; Liu, Zhong; Tian, Bing; Wang, Zhiming; Lv, Qiancheng; Luo, Bofeng; Liu, Xinting; Hu, Jun (2022 IEEE 6th Conference on Energy Internet and Energy System Integration (EI2), 2022)
Gauss integral method, Chebyshev integral method, and Gauss-Legendre integral method are the main methods used for the non-contact voltage measurement to inverse the electric field. However, these methods don't consider the influence of sensor position deviation. And the sensor position distribution might be unreasonable in these methods. Therefore, this paper proposed a novel optimized Gauss integral for transmission line voltage measurement, which combines the Gauss integral method and genetic algorithm. Furthermore, position sensitivity constraint condition is taken into the genetic algorithm. It is found that the optimized Gauss integral method improves the calculation accuracy greatly and makes the sensor distribution more reasonable for single conductors and double loop conductors, and for the catenary line, the optimized Gauss integral method used below the highest point of the catenary line is the only useful method.